Video on demand: an easy way to watch movies – studies on consumer behavior - Erminati Pancaningrum; Dify Virginia Rizaldy (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2022)
Watching movies is an activity that many people do to get rid of fatigue after doing quite tiring daily activities. In the past, watching movies could only do by going to the cinema with determined showtimes, but as technology develops grow so fast, now watching movies possible to do anytime and anywhere using video on demand. This research background is the result of pre-research which shows there is a shifting phenomenon in consumer behavior who in the beginning watched movies in theaters then switched to using on-demand services. This research has a purpose to explore the existing phenomenon, also analyze the reasons behind movie lovers use video on demand to watch movies. This research is qualitative research by using the data source as in-depth interviews with 5 informants, document collection, and triangulation of data sourcesconducted by researchers. The results of the data are analyzed using the open coding method, axial coding, and selective coding by paying attention to the aspects of trustworthiness. The result of this research shows some factors become the reasons someone watching movies uses video on demand that is; hobby, flexibility, emotional motive, patronage motive, rational motive, intrinsic motivation, extrinsic motivation, and rerun.